Cytokeratin: a Shortcut to Diagnose Spindle Cell Carcinoma - Dehghani Nazhvani A; Haddadi P; Sarafraz N; Faghihi F (Journal of Dental Biomaterial, 2017)
A relatively rare subtype of squamous cell carcinoma (SCC) is spindle cell carcinoma (SPCC). It is composed of epithelium-derived spindle cells arranged in sheets with mesenchymal properties and small, hard-ly detectable regions of SCC, challenging its definite diagnosis. We encountered five cases of SPCC. In case one, chronic inflammation and subepithelial blister with leukoplakia was found 5 years before our examination. And later, exophytic features, keratotic papules and scar with elevated margins was seen on lateral border of the tongue. In case two, three and four, an abnormal soft tissue elevations were examined, and in the fifth case we examined the soft and bony speci-men from the posterior aspect of maxillary ridge. We evaluated all of them histologically and immunohistochemically for cytokeratin to reach final diagnosis.